Knowledge, attitude, and behaviour toward same-sex sexual intercourse and HIV/AIDS prevention: A cross-sectional survey in Indonesia - Satya Wydya Yenny; Rini Gusya Liza; Syandrez Prima Putra; Rizkia Chairani Asri; Dwi Sabtika Julia; Noverika Windasari (Asian Pacific Journal of Tropical Medicine)
Objective: To assess public knowledge, attitudes, and behaviours regarding same-sex sexual intercourse (SSI) in relation to HIV/AIDS transmission prevention, especially in an inclusive cultural and religious country like Indonesia, beyond established prevention methods like safe sex practices and Pre-Exposure Prophylaxis (PrEP). Methods: We collected cross-sectional online survey data from the Indonesian 18 years or older population in December 2021 and August 2022. We determined participants' knowledge, attitude, and behaviour scores toward SSI and HIV/AIDS prevention. We critically explored each score and used multiple linear regression to identify the predictive factors. Results: The survey included 386 adults [median age (IQR): 22 (20-35) years]. The median (IQR) score was 90/100 (80-100) for knowledge, 43/50 (39-46) for attitude and 70/70 (70-70) for behaviour. The number of men who had sex with men (MSM) was 7/129 (5.4%). Male sex, non-MSM, higher knowledge, and higher attitude scores were positively associated with higher behaviour scores (P<0.001). Conclusions: This study highlights the need for inclusive HIV/AIDS prevention strategies that respect cultural and religious values, reduce stigma, and improve healthcare access, while aligning with international guidelines and scientific evidence